PB: A Message Transmission Method Based on Area Layer Division in UAV Networks - Lisong Wang; Feifei Zhu; Qing Zhou; Kui Li; Liang Liu (International Journal of Aerospace Engineering)
A search and rescue mission is a typical UAV network application scenario. In this case, it is necessary to deliver messages quickly and efficiently to the ground station through mutual cooperation between UAVs. Many methods used in this case have problems such as unbalanced popularity (the ratio of the relayed message number to the total message number) of nodes, large proportion of ping-pong effect, and long delay. In view of the above problems, this paper proposes a method named PB (Popularity Balance Method for UAVs in the same area layer) based on division of the whole search area. The method divides the search area into multiple area layers. Message transmission between area layers adopts a geographical routing manner, that is, messages are transmitted to the area layer closer to the ground station. The division of the search area changes the pattern of message transmission. Messages are delivered to the area layer closer to the destination node rather than the node closer to the destination. The pattern causes messages’ passing direction to be replaced by “point-to-point closer” to “point-to-face closer.” On the basis of message transmission at area layers, reasonable planning of UAVs’ distribution can effectively improve the network performance deterioration caused by a “hot spot.” Both analysis and experiments show that PB is superior to some existing methods in popularity balance of nodes and ping-pong effect. In addition, experiments also show that it gets better results in targets of delay, delivery rate, and hop count.